Periphyton: Ecology, Exploitation and Management 2005
DOI: 10.1079/9780851990965.0051
|View full text |Cite
|
Sign up to set email alerts
|

Periphyton in the aquatic ecosystem and food webs.

Abstract: This paper presents an in-depth insight into the role of periphyton in aquatic food webs and as a critical metabolic component of aquatic ecosystems. Energy and organic matter fluxes in general, growth regulation and habitat variables, community metabolism and links between periphyton and higher trophic levels are discussed. Recycling is also discussed as the key to nutrient fluxes and maximizing productivity of periphyton. Finally, modulation of periphyton by light availability and by mortality and losses, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…), light is the first energy source for the autotrophic community (Hill 1996) and its quantity and quality are closely related with temporal variability of primary production in rivers (Hill and Knight 1988). Different factors can influence light quality and quantity reaching biofilms (riparian vegetation, water turbidity, biofilm thickness, etc., Hill 1996) and biofilms can colonize a wide range of benthic light environments from turbid rivers under dense canopy cover to open shallow and clear streams (Wetzel 2005). In addition, in all these environments, light quantity and quality fluctuate throughout the day due to cloudy spells or movements in the riparian vegetation among others (Hill 1996).…”
Section: Introductionmentioning
confidence: 99%
“…), light is the first energy source for the autotrophic community (Hill 1996) and its quantity and quality are closely related with temporal variability of primary production in rivers (Hill and Knight 1988). Different factors can influence light quality and quantity reaching biofilms (riparian vegetation, water turbidity, biofilm thickness, etc., Hill 1996) and biofilms can colonize a wide range of benthic light environments from turbid rivers under dense canopy cover to open shallow and clear streams (Wetzel 2005). In addition, in all these environments, light quantity and quality fluctuate throughout the day due to cloudy spells or movements in the riparian vegetation among others (Hill 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Periphyton mainly consists of photosynthetic organisms (both eukaryotes and cyanobacteria) but also bacteria and fungi, can colonize any type of substratum in the photic zone, and grows imbedded within a polysaccharidic matrix (Wetzel 2001). It has been demonstrated that the contribution of periphyton to carbon fixation and nutrient cycling can be significant, particularly in lotic systems (Wetzel 2005). It can even be greater than that of phytoplankton or macrophytes in some clear shallow lakes (Liboriussen and Jeppesen 2003).…”
mentioning
confidence: 99%
“…The Gravataí river is situated in a plain region and its flow rate is low, thus increasing the flow and turbulence in the system may mean an early renewal of nutrients around the cells, favoring higher nutrient availability. Within a specific range of water turbulence and current velocity, the boundary layer thickness between the periphyton and overlying water is reduced and enhanced nutrient exchange occurs as a result (Riber & Wetzel, 1987;Wetzel, 2005).…”
Section: Discussionmentioning
confidence: 99%